Performance Budgeting (with CD) : What Works, What Doesn't. - Arnold, William G. (Berrett-Koehler Publishers, Incorporated, 2008)
Improve Your Agency's Performance Budgets and Accountability Reports Performance Budgeting: What Works, What Doesn't is a must-have resource for government officials implementing performance budgeting within their organizations. The author examines performance budgets and accountability reports from a cross-section of federal agencies and offers an objective critique of both their form and content. Examples of the best'and the worst'federal performance budgeting efforts offer insights and lessons for agency officials charged with determining the best performance budgeting techniques to put into practice. Readers will benefit from reviewing examples of other organizations' work and will learn how to use evaluation tools to apply performance budgeting techniques to their own organizations. Understand the evolution of performance budgeting and its inherent advantages Examine the performance budgets and results for eleven federal agencies Benchmark against the best agency submissions, and avoid the pitfalls of poor budgets and accountability reports Identify the attributes of good performance measures and learn how to develop them Bonus! Includes a CD-ROM with the latest performance and accountability reports for all 24 CFO agencies.